2014
DOI: 10.1007/s10753-013-9801-1
|View full text |Cite
|
Sign up to set email alerts
|

Significant Roles Played by IL-10 in Chlamydia Infections

Abstract: Chlamydia species are obligate intracellular parasites which cause usually asymptomatic genital tract infections and also are associated with several complications. Previous studies demonstrated that immune responses to Chlamydia species are different and the diseases will be limited to some cases. Additionally, Chlamydia species are able to modulate immune responses via regulating expression of some immune system molecules including cytokines. IL-10, as the main anti-inflammatory cytokine, plays important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…The role of IL-10/IL-10R signalling in Chlamydia infection is likely to be complex. While studies have shown that IL-10 supressed expression of several pro-inflammatory molecules that might be involved in immune responses against Chlamydia infections38, we and others39 have shown that Chlamydia also induces the expression of IL-10 and IL-10R. In this study we report that blocking IL-10 signalling by a homozygous knockout of IL-10RA in human iPSdMs led to increased susceptibility to C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 46%
“…The role of IL-10/IL-10R signalling in Chlamydia infection is likely to be complex. While studies have shown that IL-10 supressed expression of several pro-inflammatory molecules that might be involved in immune responses against Chlamydia infections38, we and others39 have shown that Chlamydia also induces the expression of IL-10 and IL-10R. In this study we report that blocking IL-10 signalling by a homozygous knockout of IL-10RA in human iPSdMs led to increased susceptibility to C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 46%
“…Similarly to DCs, effector CD8+ T cell response is inhibited during H5N1 viral infection by IL-10 producing CD8+ Treg cells [75,76]. The induced manipulation toward the Th2 profile assures increased surviving possibility for different infective agents, such as viruses, chlamydias, and parasites [65, 67-69, 73,74,[77][78][79]. The early IL-10 production by T cell, B cell, and monocyte/macrophage (but not on NK and DC) activation can lead to chronicity of lymphocytic choriomeningitis and B hepatitis virus infections, and the IL-10-mediated early T cell Similarly to viral infections, parasite-induced IL-10 production by various immune cells is associated with impaired resistance to protozoan and nematodes [80,81,86,87].…”
Section: Principal Immune Conditionsmentioning
confidence: 99%
“…Although MYD88-dependent signaling pathway activation results in the phosphorylation and activation of pro-inflammatory transcription factors, such as IRF3, IRF7, AP-1 and NF-kB, it also induces the PI3K/AKT pathway, which leads to upregulation of IL-10, and activates SOCS proteins [43]. IL-10 is a major anti-inflammatory cytokine [44]. SOCS proteins also suppress MAPK and JAK–STAT signaling pathways [45].…”
Section: Introductionmentioning
confidence: 99%